Dataset of the Baetidae (Ephemeroptera) and Elmidae (Coleoptera) families from the Yungas of Argentina - Albanesi, Sebastian Alejandro (2024)
The Yungas or the Subtropical Mountain Forests represent one of the most biodiverse ecoregions in Argentina. Its distribution over the Andean mountain ranges helps retain water, generating the lotic ecosystems. The aim of this work is to describe a dataset of the Baetidae and Elmidae families. This dataset contains 1,183 records, 828 belong to Baetidae (15 genera and 27 species) and 355 to Elmidae (10 genera and 16 species). Ten out of the 24 protected areas were sampled, without records in some of them, such as northeastern Salta province and eastern Jujuy province. This work is intended to expose information gaps in order to contribute to future research projects.